ANALISIS KONTRIBUSI PAJAK RESTORAN PADA PENDAPATAN ASLI DAERAH (PAD) KABUPATEN BOJONEGORO TAHUN 2017-2018 - Nurul Mazidah; Ika Pratiwi; Lailil Muf'idaf (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2019)
Restaurant Tax is one of the taxes that contributes to increasing Local Revenue, and also as regional income that can be freely used to administer local government and development. The purpose of this study was to determine the magnitude of the contribution of Restaurant Taxes to the Bojonegoro Regency's Original Revenue in 2017-2018 and the effectiveness of the realization of Restaurant Tax revenue towards the Regional Budget Revenue in Bojonegoro Regency in 2017-2018. In this study using descriptive analysis method. The results of the research conducted revealed that the effectiveness of restaurant tax collection in 2017-2018 was very effective, with an average level of effectiveness of 1.29%. The percentage contribution in 2017 was 1.32% and in 2018 it was 1.60% with an average contribution of 1.46%. The contribution of restaurant tax can be categorized as good so it must be maintained and it will be even better if it is further improved so that the contribution of restaurant tax to the PAD is greater.